(untitled) (Texas Journal of Medical Science, 2023)
Supraventricular tachycardias are paroxysmal tachyarrhythmias which require atrial or atrioventricular nodal tissue or both for their initiation and maintenance & they are often recurrent, occasionally persistent, and a frequent cause of visits to emergency rooms and primary care physicians.